And the mural stayed: memory, city and gender in the urban landscape of Madrid in the context of the rise of the new right wing (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article focus on the debate over the use of public space around the feminist mural in Ciudad Lineal as a continuity of the politics of spaces of historical memory and as part of feminist struggles over access to and enjoyment of the right to the city. Two semi-structured in-depth interviews were conducted and the position of the Vox party was ethnographically reconstructed through the analysis of interventions on official Twitter accounts. It was concluded that the dispute is framed in the struggle for decision-making in the city in general, and for who manages to inscribe memory in the space in particular, in a context in which the scarcity of specific public policies leads to a reading of the “erasure” of women's public memory by the new Spanish right as part of a political process against conquered rights.
Keywords: Right to the City, Gender, Memory, Spanish new Right